Translocal care across Kosovo's borders : reconfiguring kinship along gender and generational lines - Leutloff-Grandits, Carolin (Anthropology of Europe, 2023)
"In today's globalized world, where the foundations of home and social security are destabilized due to wars and neoliberal transformations, the villagers of Kosovo are linked with a common locality despite living across borders. By tracing long-distant family relations with a special focus on cross-border marriages, this study looks at the reconfiguration of care relations, gender and generational roles among kin-members of Kosovo, who now live in different European states"--